THE POTENTIAL OF BANANA STEM AS PLANTING MEDIA FOR KANGKUNGS (Ipomoea reptans Poir) AND MUSTARD GREENS - Avisema Sigit Saputro; Djoko Purnomo; Supriyono Supriyono (Sains Tanah - Jurnal Ilmu Tanah dan Agroklimatologi, 2017)
Banana stem water content is 90%. Therefore, it is potential as an alternative for planting media in limited agriculture lands due to their function changes. The aim of the research is to obtain information on cultivation technology and how long water content in banana stem is available for plant. This research employed the randomized block design- split plot with two treatment factors. The first factor was banana stem durations after harvest (0, 2, and four weeks) and the second one was vegetable crops, namely: kangkungs and mustard greens. Based on the treatment level, there were six combinations, and each was replicated 4 times. The research variables were height, number of leaves, chlorophyll content, nitrogen tissue, leaf area index, specific leaf area, unit price of leaves, growth rate, biomass (dry weight of the plant), length of root, and fresh weight of the plant. The result of the research shows that all treatments applied to banana stems had no effect on all variables tested. Banana stems could provide water to Ipomoea reptans Poir for the duration of 37 days after planting, and to mustards greens for the duration of 32 days after planting. Above the stated duration, the plant died due to water excess. Thus, banana stems had the potential to provide water for plants from planting to harvest, and the plants planted did not require additional watering.